1999
DOI: 10.1046/j.1365-2249.1999.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes from patients with lupus erythematosus show enhanced cytotoxicity to ultraviolet radiation and to antibody-mediated cytotoxicity

Abstract: SUMMARYKeratinocyte cytotoxicity is an important component of the immunopathology of photosensitive lupus erythematosus, and antibody-dependent cell-mediated cytotoxicity (ADCC) has been shown to be an important mechanism by which autoantibodies, especially those specific for SS-A/Ro, can induce keratinocyte damage in models of photosensitive lupus. We provide further evidence that keratinocytes from patients with photosensitive lupus show significantly greater ultraviolet radiation (UVR)-induced cytotoxicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…The ability of ultraviolet light to induce apoptotic death in suprabasal keratinocytes has been recognized for many years and these cells were called ''sunburn cells'' by morphologists (89). However, cultured keratinocytes from patients with SLE and SCLE show significantly greater cytotoxicity following UV exposure than keratinocytes from normal adult controls (67,69). There are a number of different ways whereby UV light can induce cell death in keratinocytes.…”
Section: Increased Keratinocyte Apoptosis Formation Of Neo-antigensmentioning
confidence: 99%
“…The ability of ultraviolet light to induce apoptotic death in suprabasal keratinocytes has been recognized for many years and these cells were called ''sunburn cells'' by morphologists (89). However, cultured keratinocytes from patients with SLE and SCLE show significantly greater cytotoxicity following UV exposure than keratinocytes from normal adult controls (67,69). There are a number of different ways whereby UV light can induce cell death in keratinocytes.…”
Section: Increased Keratinocyte Apoptosis Formation Of Neo-antigensmentioning
confidence: 99%
“…However, there are many studies that indicate a positive relationship between anti-Ro Aabs and CP, like the ones which measure the binding of sera containing antiRo Aabs from patients to self-derived irradiated keratinocytes [18][19][20]. These studies were always performed with sera which were tested by various techniques to be only specific for one autoantigen, among 4 or 5 different ones.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that UVr driven apoptotic keratinocytes relocate RNPs towards the cell membrane [15,16] and this event could, on a first instance, induce the production of Aabs [17]. Subsequently these circulating Aabs could bind to the apoptotic keratinocytes' membrane, producing Aabs mediated cytotoxicity, finally leading to an unwanted inflammatory response, which under normal conditions would not take place [18]. These events are proposed to be relevant in the generation of cutaneous damage in SAPs patients.…”
Section: Introductionmentioning
confidence: 99%
“…Five cases have previously been reported in the skin. [1][2][3][4][5] Here we report a case occurring in the skin of the forehead.…”
Section: Role For Trauma In Inducing Pencil ''Lead'' Granuloma In Thementioning
confidence: 99%
“…However, it has been reported that the percentage of the SLE patients who are photosensitive to ultraviolet radiation is only 60%. 4 It has also been reported that UVA1 is beneficial in several cases. 5 In our patient, phototherapy did not cause a flare of the SLE.…”
mentioning
confidence: 95%